Acute chest syndrome in sickle cell disease/HBE patient, A case report - Ibrahim Khamees (14153301) (2023)
The presented case will shed some light on one of the rarest complications of HBSE disease, which is acute chest syndrome, and will highlight the management of that complication. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.4575